Invar alloy and Invar alloy wire
The invar alloy with a tailored composition and (V, Cr)-based composite carbides effectively addresses the challenges of high strength, low tensile strength variation, and excellent torsional properties, enhancing its suitability for high-voltage electric wire core applications.
Patent Information
- Application Number
- JP2021038904
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-11
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-03-11
AI Technical Summary
Existing invar alloys face challenges in achieving high strength with minimal tensile strength variation and excellent torsional properties, particularly as ingot size increases, leading to solidification segregation and decarburization issues.
The development of an invar alloy with a specific composition, including 0.1-0.4% C, 0.05-0.20% Si, 0.1-1.0% Mn, and optimized levels of Ni, Cr, V, and other elements, which promotes the formation of (V, Cr)-based composite carbides for enhanced strength and torsional properties.
This alloy achieves high tensile strength (above 1050 MPa) with low tensile strength variation (less than 30 MPa) and superior torsional properties, attributed to the optimized hardness distribution and precipitation of (V, Cr) composite carbides.
Smart Images

Figure 0007655017000001 
Figure 0007655017000002 
Figure 0007655017000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an Invar alloy and an Invar alloy wire, and more specifically, to an Invar alloy capable of producing a wire rod having high strength, small tensile strength variation, and excellent torsional characteristics, and an Invar alloy wire using the same. [Background technology]
[0002] High-strength Invar alloys are alloys that maintain the low thermal expansion properties characteristic of Fe-Ni Invar alloys while achieving high strength through solid solution strengthening and precipitation strengthening. The main use of high-strength Invar alloys is as the core wire of high-voltage electrical wires (steel core aluminum stranded wire), which generate a lot of heat. The wire that makes up the stranded wire is twisted during the manufacturing process, so the core wire is required to have high twisting properties. In addition, the higher the strength of the high-voltage electrical wire, the wider the gap between steel towers can be and the lower the height of the steel towers can be, so the core wire is required to have higher strength.
[0003] In order to solve this problem, various proposals have been made in the past. For example, Patent Document 1 discloses an Invar alloy wire containing, by weight, C: 0.20-0.40%, Si: ≦0.8%, Mn: ≦1.0%, P: ≦0.050%, S: ≦0.015%, Cu: ≦1.0%, Ni: 35-40%, Cr: ≦0.5%, Mo: 1.5-6.0%, V: 0.05-1.0%, O: ≦0.015%, and N: ≦0.03%, with the balance being Fe and unavoidable impurities, and further satisfying Mo / V ≧1.0 and (0.3Mo+V) ≧4C.
[0004] The same document states: (a) When only V is added, coarse carbides are precipitated, whereas when Mo and V are added in combination so that Mo / V≧1.0, fine carbides are precipitated. (b) The coarsening of carbides is suppressed, thereby increasing the strength of the Invar alloy; and (c) When (0.3Mo+V)≧4C, it is possible to realize stable twisting properties while maintaining high strength. is stated.
[0005] Patent Document 2 discloses a high-strength, low-thermal expansion alloy containing, by weight, 0.1-0.4% C, 0.2-1.5% Si, 0.1-1.5% Mn, 33-42% Ni, 5.0% or less Co, 0.75-3.0% Cr, 0.2-3.0% V, 0.003% or less B, 0.003% or less O, 0.1% or less Al, 0.1% or less Mg, 0.1% or less Ti, 0.1% or less Ca, with the balance being Fe and unavoidable impurities, and satisfying the relationship 1.0%≦V+Cr≦5.0%. The same document states: (a) V has a greater effect of strengthening Fe-Ni alloys and refining carbides than Mo; and (b) V is also very effective in lowering the thermal expansion coefficient. has been disclosed.
[0006] Patent Document 3 discloses a high-strength, low-thermal expansion alloy having excellent torsional properties, which contains, by mass%, C: 0.1 to 0.4%, V: more than 0.5% to 3.0%, and Ni: 25 to 50%, satisfies 2≦V / C≦9, with the remainder being Fe and unavoidable impurities. The document describes that a certain amount of V is effective in improving twisting characteristics because it suppresses grain boundary precipitation of coarse carbides and promotes fine precipitation of intragranular carbides.
[0007] Furthermore, Patent Document 4 discloses that an Fe alloy containing 25 to 50% Ni is used to (a) In hot rolling, the alloy is heated to a temperature in the range of 1100 to 1250°C, and controlled rolling is performed so that the final rolling temperature is 900°C or higher; (b) After subsequent cold working with a reduction in area of 30 to 70%, (c) Heat treatment in the temperature range of 550 to 700°C A method for producing a high strength, low thermal expansion alloy is disclosed. The document describes that by controlling the hot rolling conditions and combining subsequent 30 to 70% cold working with heat treatment, ductility does not deteriorate even when high strength is imparted by extensive cold working.
[0008] By using the methods described in Patent Documents 1 to 4, it is possible to achieve both strength and twisting properties to a certain extent. However, when narrow-band control of strength and high twisting properties are required, it is difficult to say that conventional techniques alone can fully meet the demands. In particular, when steel ingots or steel billets are large, the variation in strength due to solidification segregation during solidification and decarburization during soaking reaches a non-negligible level. Furthermore, there have been no examples proposed in the past of an Invar alloy wire that is high strength, has small tensile strength variation, and exhibits high twisting properties. [Prior art documents] [Patent documents]
[0009] [Patent Document 1] JP 2003-082439 A [Patent Document 2] Japanese Patent Application Publication No. 07-228947 [Patent Document 3] JP 2002-256395 A [Patent Document 4] JP 2002-266025 A Summary of the Invention [Problem to be solved by the invention]
[0010] The problem to be solved by the present invention is to provide an Invar alloy having high strength and small variation in tensile strength caused by solidification segregation during solidification and decarburization during soaking, and an Invar alloy wire using the same. Another problem to be solved by the present invention is to provide an Invar alloy wire which has high strength, small variation in tensile strength, and exhibits high twisting characteristics. [Means for solving the problem]
[0011] In order to solve the above problems, the Invar alloy according to the present invention comprises: 0.1≦C≦0.4mass%, 0.05≦Si<0.20mass%, 0.1≦Mn≦1.0mass%, P≦0.05mass%, S≦0.01mass%, Cu≦1.0mass%, 30.0≦Ni≦45.0mass%, 0.3≦Cr≦2.0mass%, 0.2≦V≦1.5mass%, Al≦0.05 mass%, O≦0.015mass%, and N≦0.03mass% The remainder is Fe and unavoidable impurities. The Invar alloy is 0.05≦Mo≦ 0.3 mass% and / or 0.05≦Co≦3.0mass% It may further include.
[0012] The invar alloy wire according to the present invention is also characterized in that it is made of the invar alloy according to the present invention. The Invar alloy wire preferably satisfies the following formula (1). [Center hardness] + 10 ≧ [Surface hardness] … (1) Effect of the Invention
[0013] When an appropriate amount of Si is added to an Invar alloy having a specified composition, the adhesion of the oxide scale formed on the surface of the steel ingot during homogenization treatment is reduced. Therefore, even if a decarburized layer is formed on the surface of the steel ingot, the decarburized layer is also promoted when the oxide scale is peeled off. As a result, the increase in tensile strength variation caused by the decarburized layer can be suppressed. In addition, when a certain amount of V and Cr are added simultaneously as strengthening elements, (V, Cr)-based composite carbides are precipitated during solidification or aging treatment. (V, Cr)-based composite carbides are more easily dissolved than other carbides (e.g., Mo-based carbides). This makes it possible to perform homogenization treatment at low temperatures, and it is possible to suppress the generation of a decarburized layer and the resulting increase in tensile strength variation. Moreover, the (V, Cr)-based composite carbides precipitate isotropically and tend to precipitate finely during aging treatment, so they contribute more to improving strength than V-based carbides.
[0014] Furthermore, when such an Invar alloy is subjected to wire drawing and aging treatment under appropriate conditions, (a) A hardness distribution in which the center hardness is approximately equal to the surface hardness (hereinafter, this is also referred to as a "flat type hardness distribution"); or (b) A hardness distribution in which the center hardness is higher than the surface hardness (hereinafter, this is also referred to as an "inverted V-shaped hardness distribution") The Invar alloy wire thus obtained has high strength and small tensile strength variation, and also exhibits high twisting properties due to an optimized hardness distribution. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] An embodiment of the present invention will be described in detail below. [1. Invar alloy] [1.1. Main constituent elements] The Invar alloy according to the present invention contains the following elements, with the balance being Fe and unavoidable impurities. The types of added elements, their component ranges, and the reasons for their limitations are as follows:
[0016] (1) 0.1≦C≦0.4mass%: C is an element that contributes to strengthening the matrix of the Invar alloy, and is added in an appropriate amount. If the C content is low, the strength will be insufficient. Therefore, the C content must be 0.1 mass% or more. The C content is preferably 0.2 mass% or more. On the other hand, if the C content is excessive, the cold workability and ductility are significantly impaired. Therefore, the C content must be 0.4 mass% or less. The C content is preferably 0.35 mass% or less.
[0017] (2) 0.05≦Si<0.20mass%: Silicon is an important element for suppressing local variations in strength (variation in strength between wire rods when processed into wire rods of a specified length). The addition of silicon affects the adhesion of oxide scale formed during hot working. In general, the higher the silicon content, the higher the adhesion of oxide scale. Furthermore, when the adhesion of the scale is high, the yield is improved, but a decarburized layer tends to remain. To obtain a high yield, the silicon content must be 0.05 mass% or more. The silicon content is preferably 0.10 mass% or more. On the other hand, if the Si content is excessive, the increase in tensile strength variation due to the remaining decarburized layer becomes significant. Therefore, the Si content must be less than 0.20 mass%. The Si content is preferably 0.19 mass% or less.
[0018] (3) 0.1≦Mn≦1.0mass%: Mn is added in an appropriate amount to improve hot workability. To obtain such an effect, the Mn content must be 0.1 mass% or more. The Mn content is preferably 0.15 mass% or more. On the other hand, if the Mn content is excessive, the thermal expansion coefficient becomes high. Therefore, the Mn content must be 1.0 mass% or less. The Mn content is preferably 0.4 mass% or less.
[0019] (4) P≦0.05mass%: Since P is an element that deteriorates hot workability, it is preferable to reduce the P content as much as possible. In order to suppress the deterioration of hot workability, the P content must be 0.05 mass% or less. The P content is preferably 0.02 mass% or less.
[0020] (5) S≦0.01mass%: Since S deteriorates hot workability, it is preferable to reduce S as much as possible. In order to suppress deterioration of hot workability, the S content must be 0.01 mass% or less. The S content is preferably 0.005 mass% or less.
[0021] (6) Cu≦1.0mass%: Cu is preferably reduced as much as possible to increase the thermal expansion coefficient. In order to suppress an increase in the thermal expansion coefficient, the Cu content must be 1.0 mass% or less. The Cu content is preferably 0.2 mass% or less.
[0022] (7) 30.0≦Ni≦45.0mass%: Ni is an important element that contributes to the reduction of the thermal expansion coefficient due to the Invar effect of the Fe-Ni alloy. If the Ni content is too low, the Invar effect becomes insufficient. Therefore, the Ni content must be 30.0 mass% or more. The Ni content is preferably 35.0 mass% or more. Similarly, if the Ni content is excessive, the Invar effect becomes insufficient. Therefore, the Ni content must be 45.0 mass% or less. The Ni content is preferably 41.0 mass% or less.
[0023] (8) 0.3≦Cr≦2.0mass%: Cr is expected to strengthen the precipitation by forming a composite carbide with V. A (V, Cr)-based composite carbide can improve strength while minimizing adverse effects on twisting properties compared to a carbide of V alone. Therefore, Cr is actively added in the present invention. If the Cr content is low, the strength becomes insufficient. Therefore, the Cr content must be 0.3 mass% or more. On the other hand, if the Cr content is excessive, the thermal expansion coefficient becomes high. Therefore, the Cr content must be 2.0 mass% or less. The Cr content is preferably 1.0 mass% or less.
[0024] (9) 0.2≦V≦1.5mass%: V is an element that contributes to precipitation strengthening by forming carbides. Unlike Mo, V has only minor segregation and can be homogenized at a low temperature, so it is actively added. If the V content is too low, improvement in strength cannot be expected. Therefore, the V content must be 0.2 mass% or more. The V content is preferably 0.3 mass% or more. On the other hand, if the V content is excessive, the thermal expansion coefficient becomes high. Therefore, the V content must be 1.5 mass% or less. The V content is preferably 1.2 mass% or less.
[0025] (10) Al≦0.05mass%: Al may be added as a deoxidizer. However, if the Al content is excessive, the thermal expansion coefficient increases. Therefore, the Al content must be 0.05 mass% or less. The Al content is preferably 0.03 mass% or less.
[0026] (11) O≦0.015mass%: O affects the amount of oxide inclusions produced. In general, the more inclusions there are, the more adversely they affect the twisting properties, so the lower the O content, the better. To obtain high twisting properties, the O content must be 0.015 mass% or less.
[0027] (12) N≦0.03mass%: N affects the amount of nitride inclusions produced. In general, the more inclusions there are, the more adversely they affect the twisting properties, so the lower the N content, the better. To obtain high twisting properties, the N content must be 0.03 mass% or less.
[0028] [1.2. Sub-constituent elements] In addition to the above-mentioned main constituent elements, the Invar alloy according to the present invention may further contain one or more of the following elements. The types of the added elements, their component ranges, and the reasons for their limitations are as follows:
[0029] (13) 0.05≦Mo≦1.5mass%: Mo may be added since it is an element that contributes to precipitation strengthening by forming carbides. In order to obtain such an effect, the Mo content is preferably 0.05 mass% or more. However, if the Mo content is excessive, segregation becomes significant and a high-temperature treatment is required in the homogenization treatment. Therefore, the Mo content is preferably 1.5 mass% or less. The Mo content is more preferably less than 0.2 mass%.
[0030] (14) 0.05≦Co≦3.0mass%: Co is an element that contributes to a decrease in the thermal expansion coefficient due to the Invar effect, similar to Ni. In order to obtain such an effect, the Co content is preferably 0.05 mass% or more. However, since Co is a very expensive element compared to Ni, an excessive Co content increases the cost, and therefore the Co content is preferably 3.0 mass% or less.
[0031] (15) 0.001≦B≦0.05mass%: (16) 0.001≦Mg≦0.05mass%: (17) 0.001≦Ca≦0.05mass%: B, Mg, and Ca all contribute to improving the hot workability of the Fe-Ni Invar alloy. Therefore, the Invar alloy may contain one or more of these elements. To obtain the above-mentioned effects, the content of each of these elements is preferably 0.001 mass% or more. However, if the contents of these elements are excessive, the thermal expansion coefficient becomes high. Therefore, the contents of B, Mg, and Ca are each preferably 0.05 mass% or less.
[0032] (18) 0.001≦Ti≦0.2mass%: (19) 0.001≦Nb≦0.2mass%: (20) 0.001≦Ta≦0.2mass%: Ti, Nb, and Ta all form carbides by aging treatment and contribute to improving strength. Therefore, the Invar alloy may contain one or more of these elements. In order to obtain the above-mentioned effects, the content of each of these elements is preferably 0.001 mass% or more. However, if the contents of these elements are excessive, the thermal expansion coefficient becomes high. Therefore, the contents of Ti, Nb, and Ta are each preferably 0.2 mass% or less.
[0033] [2. Invar alloy wire] The Invar alloy wire according to the present invention is made of the Invar alloy according to the present invention.
[0034] [2.1. Composition] The composition of the Invar alloy is as described above, and therefore a detailed description thereof will be omitted.
[0035] [2.2. Characteristics] 2.2.1. Tensile strength The Invar alloy wire according to the present invention exhibits high tensile strength because (V, Cr)-based composite carbides are precipitated by aging treatment. Specifically, when the components and manufacturing conditions are optimized, the tensile strength becomes 1050 MPa or more. When the components and / or manufacturing conditions are further optimized, the tensile strength becomes 1150 MPa or more, or 1200 MPa or more.
[0036] [2.2.2. Tensile strength variation] "Tensile strength variation" refers to the difference between the maximum and minimum tensile strength values when a tensile test is conducted using 10 tensile test pieces (JIS No. 9B) produced under the same conditions. The Invar alloy according to the present invention has a small tensile strength variation because the remaining decarburized layer is suppressed. Specifically, when the components and manufacturing conditions are optimized, the tensile strength variation is 30 MPa or less. When the components and / or manufacturing conditions are further optimized, the tensile strength variation is 25 MPa or less, or 20 MPa or less.
[0037] [2.2.3. Hardness distribution] When an Invar alloy with optimized components is subjected to wire drawing and aging treatment under appropriate conditions, an Invar alloy wire with a flat or inverted V-shaped hardness distribution can be obtained. Specifically, when the components and manufacturing conditions are optimized, an Invar alloy wire with a hardness distribution that satisfies the following formula (1) can be obtained. [Center hardness] + 10 ≧ [Surface hardness] … (1) Here, the "center hardness" refers to the average value of Vickers hardness measured at any five points within a region of a radius of 1 mm or less from the center of the wire. "Surface hardness" refers to the average Vickers hardness measured at any five points within a region extending 0.2 mm from the surface of the wire.
[0038] In order to obtain high twisting properties, it is particularly preferable that the Invar alloy wire satisfies the following formula (2). [Center hardness]>[Surface hardness]+10 …(2)
[0039] [3. Manufacturing method of Invar alloy wire] The Invar alloy wire according to the present invention is (a) Melt and cast the raw materials mixed to obtain the desired composition, (b) subjecting the obtained steel ingot to a homogenization treatment; (c) The homogenized steel ingot is subjected to hot working. (d) subjecting the hot worked billet to hot wire rolling; (e) The hot-rolled rough wire is subjected to solution heat treatment as necessary; (f) cold drawing the solution-treated rough wire; (g) Aging treatment is performed on the cold drawn wire. It can be produced by the above method.
[0040] [3.1. Melting and casting process] First, the raw materials mixed to obtain a desired composition are melted and cast (melting and casting process). The method and conditions for melting and casting are not particularly limited, and the most suitable method and conditions can be selected depending on the purpose.
[0041] [3.2. Homogenization process] Next, the obtained steel ingot is subjected to homogenization treatment (homogenization treatment step). The homogenization treatment is carried out in order to remove segregation that occurs during casting. The conditions of the homogenization treatment are not particularly limited as long as such effects are achieved. In the present invention, since the Mo content is limited, the homogenization treatment can be carried out at a relatively low temperature. Specifically, the homogenization treatment is preferably carried out by heating and holding the steel ingot under the conditions of a temperature of 1200°C to 1300°C for a time of 4 hours to 36 hours.
[0042] [3.3. Hot working process] Next, the homogenized steel ingot is hot worked (hot working step). The hot working is carried out in order to destroy the coarse cast structure, refine the structure, and give the steel ingot a shape suitable for hot wire rolling. When the steel ingot is subjected to hot wire rolling, it is usually hot worked into a billet with a square cross section.
[0043] [3.4. Hot wire rolling process] Next, the hot-worked billet is subjected to hot wire rolling (hot wire rolling process). Hot wire rolling is performed to make the billet into a rough wire having a predetermined diameter. The diameter of the rough wire is selected so that drawing at a predetermined area reduction rate is possible in the cold wire drawing process described below. Other rolling conditions are not particularly limited, and optimal conditions can be selected depending on the purpose. After hot wire rolling, it is preferable to rapidly cool the rough wire. This is to suppress reprecipitation of carbides during the cooling process.
[0044] [3.5. Solution heat treatment process] Next, the hot-rolled rough wire is subjected to solution heat treatment as necessary (solution heat treatment step). The solution heat treatment is preferably performed when the (V, Cr)-based composite carbides are not sufficiently dissolved, and by doing so, the precipitation of the (V, Cr)-based composite carbides in the aging treatment step becomes sufficient. The conditions of the solution heat treatment are not particularly limited as long as such effects are obtained. In the present invention, since the content of Mo is limited, the solution heat treatment can be performed at a relatively low temperature. Specifically, the solution heat treatment is preferably performed by heating and holding the rough wire under the conditions of a temperature of 1050°C to 1250°C and a time of 0.5 hr to 2 hr, and then cooling it. Examples of the cooling method include air blast cooling, oil cooling, and water cooling. After the solution heat treatment, pickling is performed to remove oxide scale.
[0045] [3.6. Cold wire drawing process] Next, the solution-treated rough wire is subjected to cold drawing (cold wire drawing process). In general, the smaller the die angle of the die used in the wire drawing process, the easier it is to obtain an Invar alloy wire with a flat or inverted V-shaped hardness distribution. However, if the die angle is too small, the contact time between the rough wire and the die becomes long, making the wire more susceptible to breakage. Therefore, during cold wire drawing, it is necessary to provide sufficient lubrication between the rough wire and the die. The area reduction rate during cold drawing is not particularly limited, and an optimal value can be selected depending on the purpose.
[0046] [3.7. Aging treatment process] Next, the cold drawn wire is subjected to an aging treatment (aging treatment step). In this way, an Invar alloy wire according to the present invention is obtained. The aging treatment is performed to precipitate (V, Cr)-based composite carbides in the matrix and to make the hardness distribution flat or inverted V-shaped. The conditions of the aging treatment are not particularly limited as long as such effects are achieved. Specifically, the aging treatment is preferably performed by heating and holding the wire under the conditions of a temperature of 450°C to 750°C and a time of 2 hours to 12 hours.
[0047] [4. Effect] [4.1. Suppression of decarburization] In order to suppress the tensile strength variation of high-strength Invar alloys, it is essential to mitigate solidification segregation through homogenization treatment. However, the high-temperature heat treatment may cause decarburization. The decarburized layer remains even after product rolling and may be a factor in causing the tensile strength variation of the wire rod. As a result of extensive research to suppress decarburization, it was found that by setting the Si content within a specified range, the adhesion of the oxide scale generated during homogenization treatment is reduced, making it possible to mitigate the persistence of the decarburized layer.
[0048] [4.2. Improving strength stability by suppressing segregation and increasing strength by controlling carbide constituent elements] In addition to the main components Fe and Ni, high-strength Invar alloys contain Cr, Mo, and V, which form precipitated carbides. Of these, Mo is particularly susceptible to solidification segregation. In addition, the homogenization process required to alleviate segregation requires high temperatures of around 1300°C. Therefore, when considering the regional variation in strength characteristics and manufacturability, the addition of Mo is not desirable.
[0049] On the other hand, although V does solidify and segregate, the solidification segregation is not as significant as that of Mo, and the homogenization temperature required for segregation relaxation is relatively low. Therefore, V has favorable conditions as a carbide constituent element. In addition, a solution heat treatment may be performed as an intermediate heat treatment to dissolve carbides that are unintentionally precipitated during the manufacturing process of this alloy. In this case, V-based carbides also contribute to the stability of properties in that they are easily dissolved. However, compared to (V, Cr)-based composite carbides, V-based carbides do not contribute much to improving strength. Therefore, in the present invention, the (V, Cr)-based composite carbides are actively utilized, and the optimal components and process for stabilizing strength properties have been found.
[0050] [4.3. Hardness distribution control through manufacturing process optimization] A major application example of high-strength Invar alloys is the core wire of a high-voltage cable. For this application, not only strength but also torsional properties (resistance to fracture due to torsional deformation) are required. Focusing on the local deformation amount in torsional deformation, it is known that torsional deformation is a unique deformation mechanism in which the deformation amount is small at the center of the wire cross section, but increases as it approaches the surface. Therefore, the radial hardness distribution is an important factor in improving torsional properties. In general, the greater the distribution of hardness at the center compared to the hardness of the surface layer (inverted V-shaped hardness distribution), the more excellent the torsional properties tend to be. To realize such a hardness distribution in a mass production process, it is necessary to finely control each manufacturing process condition. The present inventors have found a preferable manufacturing process as a result of intensive research. An example is shown below.
[0051] First, a billet soaked at 1200°C or higher is wire-rolled and quenched. Quenching is preferred because it suppresses the reprecipitation of carbides during the cooling process. If water-cooling is possible, the quenching process is preferably water-cooled. Then, if necessary, a solution heat treatment is performed at 1050°C or higher and 1250°C or lower, and pickling is performed to remove oxide scale from the surface. Then, cold drawing is performed with a reduction in area of 30 to 90%. At this time, it is preferable to use a cold drawing die with a die angle of 5° to 15°.
[0052] In normal cold drawing, high-angle dies (here, for convenience, dies with a die angle of 12° or more) are often used, which are advantageous for drawing in lubricants. However, when processing is performed only with high-angle dies, processing strain is concentrated in the surface layer, making it difficult to obtain the desired hardness distribution. Therefore, by using low-angle and high-angle dies in combination, processing strain is introduced deep into the material, and a flat or inverted V-shaped hardness distribution can be obtained by subsequent aging treatment at 450 to 750°C. EXAMPLES
[0053] ( Examples 1 to 6, Reference Examples 7 to 8, Examples 9 to 10, Reference Examples 11 to 12, Examples 13 to 25, Reference Examples 26 to 27 , Comparative Examples 1 to 12) [1. Sample preparation] A 2.5 t steel ingot having the composition shown in Table 1 was melted in a vacuum induction furnace. This was subjected to homogenization treatment and then hot rolling to produce a rough wire having a diameter of 14 mm. This rough wire was subjected to solution heat treatment in the temperature range of 1100°C to 1180°C and quenched. Furthermore, the wire was drawn to a diameter of 8 mm using cold drawing dies with die angles of 12° and 7°. The obtained wire was then subjected to aging treatment at 550°C to 670°C.
[0054] [Table 1]
[0055] 2. Test Method [2.1. Tensile test of wire rod after aging treatment] Ten JIS 9B tensile test pieces were prepared from each wire after aging treatment, and their tensile strength and total elongation were measured and the average was calculated. The tensile strength variation was calculated from the difference between the maximum and minimum tensile strength values. Tensile strengths of 1050 MPa or more were rated as "○ (pass)", and those less than 1050 MPa were rated as "× (fail)". Tensile strength variations of 30 MPa or less were rated as "○ (pass)", and those exceeding 30 MPa were rated as "× (fail)". Furthermore, total elongation of 0.8% or more was rated as "○ (pass)", and those less than 0.8% were rated as "× (fail)".
[0056] [2.2. Evaluation of wire characteristics after Al cladding] Examples 1 to 6, Reference Examples 7 to 8, Examples 9 to 10, Reference Examples 11 to 12, Examples 13 to 25, Reference Examples 26 to 27 For the wire, Al cladding was applied to the wire surface after aging treatment so that the cross-sectional area ratio was about 20%. The Al-clad wire was then further drawn to a diameter of 3.8 mm. The obtained material was subjected to Vickers hardness measurement, twisting test, and thermal expansion coefficient measurement under the following conditions.
[0057] [2.2.1. Vickers hardness measurement] The Vickers hardness of the cross section was measured five times at a position 0.2 mm from the surface of the Invar alloy part and at the center, and the average value was calculated. The average hardness of the surface part was defined as the "surface hardness" and the average hardness of the center part was defined as the "center hardness", and they were evaluated according to the following criteria. A (Pass): [Center hardness] > [Surface hardness] + 10 B (Pass): |[Center hardness]-[Surface hardness]|≦10 C (Fail): [Surface hardness]>[Center hardness]+10
[0058] [2.2.2. Twist test] The torsion test was carried out with a gripping distance of 100D (380mm) and a speed of about 60 rotations per minute, with tension applied to the specimen so that it would not sag. A test specimen that was twisted 50 times or more before breaking was rated as "A grade (pass)", 20 times or more was rated as "B grade (pass)", and less than 20 times was rated as "C grade (fail)".
[0059] [2.2.3. Thermal expansion coefficient measurement] The thermal expansion coefficient was measured in the temperature range of 15°C to 290°C. The thermal expansion coefficient from 15°C to 230°C was 3.7×10 -6 ℃ -1 and the thermal expansion coefficient between 230℃ and 290℃ is 10.8×10 -6 ℃ -1 Those that satisfied the following criteria were marked as "○ (pass)", and those that did not were marked as "× (fail)".
[0060] [3. Results] [3.1. Tensile test of wire rod after aging treatment] The results of the tensile test of the wire rod after aging treatment are shown in Table 2. The following can be seen from Table 2. (1) In Comparative Examples 1 to 3, the Si content was excessive, which resulted in significant decarburization, and therefore large variations in tensile strength. (2) Comparative Examples 4 to 9 have low tensile strength due to an insufficient Cr content. (3) In Comparative Examples 10 and 12, since no V was added, the tensile strength was low. (4) In Comparative Example 11, the V amount is excessive, so the total elongation is small. (5) Examples 1 to 6, Reference Examples 7 to 8, Examples 9 to 10, Reference Examples 11 to 12, Examples 13 to 25, Reference Examples 26 to 27Since the components of each of these are optimized, they have high tensile strength, small tensile strength variation, and large total elongation. Reference examples 26~27 Since the amount of Mo is large, the strength is higher than that of the other examples.
[0061] [Table 2]
[0062] [3.2. Evaluation of wire characteristics after Al cladding] The characteristics of the wire after Al cladding are shown in Table 3. From Table 3, the following can be seen. (1) Examples 1 to 6, Reference Examples 7 to 8, Examples 9 to 10, Reference Examples 11 to 12, Examples 13 to 25, Reference Examples 26 to 27 The hardness distribution of all wires was flat (grade B) or inverted V-shaped (grade A). Therefore, all of them showed high twisting properties. Wires with inverted V-shaped hardness distribution tended to have higher twisting properties than flat wires. (2) Examples 1 to 6, Reference Examples 7 to 8, Examples 9 to 10, Reference Examples 11 to 12, Examples 13 to 25, Reference Examples 26 to 27 It was found that all of the wires have a small thermal expansion coefficient and maintain the Invar effect.
[0063] [Table 3]
[0064] Although the embodiment of the present invention has been described in detail above, the present invention is not limited to the above embodiment, and various modifications are possible without departing from the gist of the present invention. [Industrial Applicability]
[0065] The Invar alloy according to the present invention can be used for the core wire of a high-voltage electrical cable.
Claims
1. 0.1≦C≦0.4mass%, 0.05≦Si<0.20 mass%, 0.1≦Mn≦1.0 mass%, P≦0.05mass%, S≦0.01mass%, Cu≦1.0mass%, 30.0≦Ni≦45.0mass%, 0.3≦Cr≦2.0mass%, 0.2≦V≦1.5mass%, Al≦0.05 mass%, O≦0.015 mass%, and N≦0.03mass% and the balance being Fe and unavoidable impurities.
2. The Invar alloy according to claim 1, further comprising 0.05≦Mo≦0.3 mass%.
3. The Invar alloy according to claim 1 or 2, further comprising 0.05≦Co≦3.0 mass%.
4. 0.001≦B≦0.05mass%, 0.001≦Mg≦0.05 mass%, and 0.001≦Ca≦0.05mass% The Invar alloy according to any one of claims 1 to 3, further comprising one or more elements selected from the group consisting of:
5. 0.001≦Ti≦0.2mass%, 0.001≦Nb≦0.2 mass%, and 0.001≦Ta≦0.2mass% The Invar alloy according to any one of claims 1 to 4, further comprising one or more elements selected from the group consisting of:
6. An Invar alloy wire made of the Invar alloy according to any one of claims 1 to 5.
7. The Invar alloy wire according to claim 6, wherein the tensile strength variation is 30 MPa or less. The "tensile strength variation" refers to the difference between the maximum and minimum tensile strength values when a tensile test is conducted using 10 tensile test pieces (JIS No. 9B) prepared under the same conditions.
8. The Invar alloy wire according to claim 6 or 7, which satisfies the following formula (1): [Center hardness] + 10 ≧ [Surface hardness] ... (1) However, the "center hardness" refers to the average value of Vickers hardness measured at any five points within a region of 1 mm radius from the center of the wire, The "surface hardness" refers to the average value of Vickers hardness measured at any five points within a region extending from the surface of the wire to 0.2 mm.
Citation Information
Patent Citations
Alloy with high strength and low thermal expansion
JP1995228947A
High strength and low thermal expansion alloy having excellent twisting and alloy wire thereof
JP2002256395A
Method for producing high strength and low thermal expansion alloy having excellent ductility
JP2002266025A
Invar alloy wire having excellent strength and twisting property, and production method therefor
JP2003082439A
High strength and low thermal expansion alloy wire
WO2018193810A1